EVALUASI HASIL REKLAMASI TAMBANG RAKYAT PUMICE DI DESA WAJEGESENG KABUPATEN LOMBOK TENGAH NUSA TENGGARA BARAT = EVALUATION ON RECLAMATION ACTIVITIES OF SMALL SCALE MINING OF PUMICE IN... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The pumice mining activities in Lombok island were started in the year of 1986, which was initially collected it from land surface. Since 1989, the people mining activities have spread out in almost Lombok island by diging and using simple equipments. The lack of education of people has caused the mining activities uncontrolled and caused surface land damage. To evaluate the influence of reclamation an investigation was done in 100 mining locations. The impact of pumice mining activities on landuse in research area has decreased are the soil vertilities, varities of specific vegetation, microclimate disturbances and erotion has increased. The reclamation activities have been done by the [and owner, the Evaluation Result indicated that land settlement, waste management, handling of erosion and revegetation did not satisfy yet. The small size of pumice waste can be used as a raw material of building material i.e. bataco brick, light roof tile and polishing ash. In the other sides, the unused pumice which has heavy density can be used as building foundation and terrace bank material. The land owners prefer to plant mangosteen, durio and banana for revegetation. This activity has been matched to planological landuse program, soil condition and well organized management, which have been supported by the government.